FGFR4 inhibitors for the treatment of hepatocellular carcinoma: a synopsis of therapeutic potential. (3rd April 2022) - Xie, Hao; Alem Glison, Diego M; Kim, Richard D.
ABSTRACT: Introduction: The mainstay pharmacological approaches to patients with hepatocellular carcinoma (HCC) are tyrosine kinase inhibitors, antiangiogenic agents, and immune checkpoint inhibitors in combination therapy. Aberrant signaling of fibroblast growth factor 19 (FGF19) and its corresponding receptor, fibroblast growth factor receptor 4 (FGFR4), are a driver of HCC cell growth and survival. However, the clinical potential of agents targeting aberrant FGF19/FGFR4 signaling has not been adequately explored. Areas covered: We evaluate the existing literature on aberrant signaling of FGF19/FGFR4 in HCC and address the recent preclinical and clinical advances of selective FGFR4 inhibitors in the treatment of advanced HCC. Our literature search was performed in September 2021 on clinical trials and ongoing studies published in journals or presented in conferences for cancer research. Expert opinion: Preclinical studies show selective FGFR4 inhibitors to be highly potent. These inhibitors also show promise in clinical trials and demonstrate manageable on-target side effects. An emphasis should be placed on the development of predictive biomarkers and on enhancing the understanding of primary and acquired resistance mechanisms. This will inspire rationale combination therapy strategies for testing in future clinical trials.